Information security in Logistics 4.0: a bibliometric study (Research, Society and Development, 2020)
The objective of this paper was to identify the level of  information security importance that Logistics 4.0 has demanded analyzing the international scientific literature. The Google Scholar and CORE databases were consulted, and the search period was from 2014 to 2019. This study is an exploratory and descriptive research that used bibliometrics and cognitive computing. Thirty-three publications were selected and addressing information security, internal industrial logistics and Logistics 4.0. There is opportunity to develop tools that help to preserve the security of information shared with the supply chain.